Inclusive Communication: A starting point for educational care with people with complex communication needs and minority diseases - Calleja-Reina, Marina; Rodríguez-Santos, José Miguel; Luque-Liñán, María Luisa (My University, 2022)
ABSTRACT The purpose of this work is to identify the modes of communication of people with complex communication needs (CCN) and minority diseases (MIDI) as a starting point for inclusive communication in the educational environment. The procedure was carried out by means of an online survey in three languages aimed at parents and professionals working with this population. Information was obtained from 87 people with various diagnoses of MIDI, CCN and Severe Intellectual Disability (SID). 51 were male (58.6%) and 36 were female (41.4%), aged 2-48 years (M =13., SD =10.78). Data were collected in several countries (some Latin American countries, Spain and the United States). 93.1% were parents and 6.9% were professionals working with the target population. The results show that people with CCN-MIDI do not speak but vocalise, laugh, shout and use facial expressions when they want to communicate (in 67.1% of cases). They are able to produce single words (in 59.7% of cases). The few vocal-verbal utterances are characterised by no or very little intelligibility of the verbal utterances, which is why they are understood by their immediate environment (70.1%). They show verbal stereotypies, i.e. repetition of words, phrases or melodies (59.7%), immediate echolalia (57.5%) and delayed echolalia (45.6%). People communicate using AAC with low-tech aids based on pictograms (62.0%), followed by picture communication boards (53.9%) or manual signs with linguistic value (52.8%). AAC systems such as Cued speech (25.3%), total communication (29.9%) or Makaton (31.0%) or apps for mobile phones or tablets (35.7%) are less used.
Keywords: Educación inclusiva - Congresos; Comunicación - Trastornos - Congresos; Competencia comunicativa - Congresos; Inclusive communication; Educational Care; Complex communication needs; Rare diseases